Potensi Pemanfaatan Limbah Peternakan Sapi Pedaging di SPR (Sekolah Peternakan Rakyat) Ngudi Rejeki, Kabupaten Kediri - Septian Bima Fajar Prambudi; Salundik; Muladno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Waste is used material or leftovers from an activity or production process whose function has changed from the original. Livestock waste directly has a negative impact on residents in the Ngudi Rejeki School for Smallholder Community area. The Ngudi Rejeki SPR is located in Ngadiluwih Village, Kediri Regency. The main commodity produced from the Ngudi Rejeki SPR is a beef cattle with a maintenance period of around 4-6 months. The method used in this study is through direct interviews with informants and, joint discussions, and verification of data with the literature. There are various problems that arise, especially the pungent odor resulting from the waste produced so that it becomes a complaint for local residents. Some breeders have utilized waste such as biogas and fish feed, but the amount is very small. Therefore, breeders' awareness is needed to process the waste produced so that it is not wasted but it can also be used to get income and reduce pollution that occurs. Based on research conducted, it is found that about 1.8 tons of waste is produced every day from beef cattle farmers in the Ngudi Rejeki SPR, but it has not been maximally utilized. Some examples of waste utilization that can be done include making organic fertilizer, biogas, and fish feed. This Research aims to analyze the waste potention from the fattening cattle farm that can used in SPR Ngudi Rejeki. Keywords: School for Smallholder Community, Waste, Biogas, Fertilizer, Fish Feed